Improving (not perfecting) tax legislation: rules and principles revisited - Freedman, J (Sweet & Maxwell, 2010)
This article revisits the arguments made by John Avery Jones in 1996 for ?less detailed legislation interpreted in accordance with principles.? His plea has been influential but perhaps not completely understood. Recent developments in the UK, particularly in the area of so-called ?principles-based drafting? may not have assisted in promoting this cause. It is frequently argued that real improvements in tax law require a coherent underlying policy, not just drafting changes. Obviously, drafting techniques will not cure a poorly structured tax and so ideally the starting point would be improved policy. But we cannot afford to wait for a total policy overhaul. A different approach to the way we legislate could both improve the way we think about policy and result in better implementation, application and legitimacy in decision making. Principles-based drafting is not a solution to all ills. Nevertheless, it could offer one route, in appropriate cases, to improvement as well as, in other cases, highlighting the need for more fundamental reform. We should not give up this experiment simply because it has not yet delivered total success. No new drafting technique can deliver a perfect tax system, but it is worth persevering with principles-based legislation.